Introduction of the first dean of the Faculty of Physical Culture - Bohuslav Hodaň (Palacky University, 2010)
Dear colleagues! We are honored by your visit to our Faculty of Physical Culture on the occasion of our traditional "Movement and Health" conference. Interestingly, it has only been twenty years since our faculty was established. The answer to the question of whether this time is long or short, is very relative. It depends on the quality of work and the quantity of success achieved. Although the activities of our faculty are aimed in various directions, one idea is common for all - our general orientation on the relationships between a human's movement and his/her health. This orientation is from the beginning of our faculty respected. The conference "Movement and Health" is always aimed at specific problems which are the leading representative of this orientation. We are very satisfied that they evoke the hopeful feedback from the scientific world. So, this year's conference is the sixth, and it is the contemporary effect of our long term work, to which many colleagues have contributed. At the head of the preparation and on the leadership of the conferences were many colleagues of our faculty. However, if we are speaking about the success of our conferences, it is also necessary to speak about our guests. The preparation of some event can have potential, but without the quality of its guests, its success is not possible. That is why we can state, with satisfaction, that we have always had the honor to welcome many respected colleagues from around the world. Many of these guests are in collaboration with the significant national as well as international organizations, and this important international cooperation also started due to these conferences. We are also very glad and honored that in this year we have the opportunity to welcome the important representatives of many institutions and the representatives of respected organizations. We hope that your stay in Olomouc and at our Faculty of Physical Culture will be pleasant and successful. In conclusion, we would like to express one great ambition - to transfer our scientific knowledge in practical forms and to really contribute to the health of the whole population.